BioLogin a Java-based module on biometric authentication--an OpenMRS extension - Dela Peña, O.
BioLogin: A Java-based Module on Biometric Authentication-An Open MRS Extension aims to implement a more secure user authentication on OpenMRS, an open-source electronic medical record system (EMRS). The project aims to provide users of the medical record system an alternative to traditional username-password logging on scheme by using additional log-in credentials by using fingerprint. The project only concerns itself on the authentication and does not necessarily affect the core of the records systems and the other features it contains (i.e. database schema, framework, access control, etc.)